Carbon Footprint of Universitas Airlangga Before and During the Covid-19 Pandemic - Permata Hajjarianti; Nurina Fitriani; Lauditta Chavia Zagita; Devi Ana; Trisnadi Widyaleksono; Agoes Soegianto; Wahid Dianbudiyanto; Karnaji Karnaji; Muhammad Miftahussurur (Universitas Diponegoro, 2023)
This study focus on calculating the carbon footprint from the activities of the Universitas Airlangga. CO2 emission calculations were carried out using the UI GreenMetric method and the Intergovernmental Panel on Climate Change (IPCC) in two periods: before the Covid-19 pandemic and during the Covid-19 pandemic. Activities at Universitas Airlangga that produce carbon footprints are divided into two main sources, first, primary sources that come from direct combustion of fuel into energy, such as burning fuel in motorized vehicles and a secondary source that comes from an indirect source of using electricity in the campus area. The results showed that in the period before the pandemic, the total carbon emissions, based on the IPCC calculation method, were 23.830,34 tons of CO2-eq/year. Meanwhile, based on the UI GreenMetric method, a total carbon emission of 26.325,36 tons of CO2-eq/year was obtained. As for the time period during the pandemic, Universitas Airlangga's total carbon emissions obtained based on the IPCC calculation method were 20.506,69 tons of CO2-eq/year. Meanwhile, based on the UI GreenMetric method, a total carbon emission of 22.321,63 tons of CO2-eq/year was obtained. Secondary carbon footprint mapping is carried out to ascertain the distribution of secondary CO2 emissions produced by Universitas Airlangga. The secondary carbon footprint both before and during the Covid-19 pandemic was mostly generated by the Universitas Airlangga Hospital.